Some patterns of development radio-induced metachronous tumors - A. V. Vazhenin; N. A. Shanazarov; E. L. Shun’ko (Вестник рентгенологии и радиологии, 2016)
Objective: to determine the specific features of the development of metachronous tumors and survival rates in patients with metachronous primary and multiple cancers after radiotherapy for the first tumor.Material and methods. The archival data of the Chelyabinsk Regional Oncology Dispensary on the treatment of 232 patients, in whom metachronous primary and multiple tumors occurred after radiotherapy for primary tumor, were studied.Results. The patients’ mean age at the diagnosis of the first tumor was 60.23 years (95% CI 58,75–61,72). The time from the first tumor to the second one averaged 91.81 months (95% CI 80,57–103,05). The patients survived for an average of 129.41months (95% CI 116,55–142,28) after the diagnosis of the first tumor and 37.64 months (95% CI 31,92–43,35) after the occurrence of the second tumor. Overall, the patients survived for an average of 127.03 months (95% CI 114,02–140,03) followingradiotherapy for the first tumor. According to the classification, the authors identified three metachronous tumor subgroups: multicentric multiple tumors in one organ (16.0%), systemic tumors and tumors of paired organs (15.5%), and nonsystemic multiple tumors of different organs (68.5%).Conclusion. Patients with multicentric metachronous multiple tumors in one organ are younger and have the shortest time from the diagnosis of the first tumor to the emergence of the second one and the longest survival after the diagnosis of the firsttumor, that after the detection of the second tumor and that after the initiation of radiotherapy. Patients with nonsystemic multiple tumors in different organs areolder and have the longest time from the diagnosis of the first tumor to the occurrence of the second one and the shortest survival.